Isolation and identification of different compounds from Citrus assamensis leaf (Journal of Bangladesh Academy of Sciences, 2021)
Six coumarins, one benzene, one flavone, one acridone, one limonoid, one triterpene and two phytosterol derivatives were isolated from the methanol, ethanol and chloroform leaf extracts of Citrus assamensis. Extensive spectroscopic studies, including high field 1H NMR and 13C NMR analyses, allowed the identification of thirteen known compounds as bergapten (1), umckalin (2), citropten (3), 4-hydroxybenzaldehyde (4), bergamottin (5), β-amyrin (6), umbeliferone (7), scopoletin (8), citrusinol (9), citracridone-III (10), limonin (11), stigmasterol (12), and β-sitosterol (13). The identity of these compounds was confirmed by comparison with published data as well as co-TLC with authentic samples.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 85-93, 2020